Chemical Composition and Biological Activity of the Essential Oil of Campanula olympica Boiss. - Tosun, Gonca; Kahriman, Nuran; Çoskunçelebi, Kamil; Genc, Hasan; Alpay Karaoglu, Sengül; Yayli, Nurettin (Asian Journal of Chemistry, 2011)
The present work describes the chemical composition and antimicrobial activity of the essential oil of Campanula olympica Boiss. which was isolated from the all parts of the plant by hydrodistillation and analyzed by GC-FID and GC-MS. Nineteen components representing 94.0 % of the total oil were characterized and the main components of this specie were found to be 2E,6Z-farnesol (14.8 %), 3,3-dimethyl-2[5-methoxy-3-methyl-2-pentylidenen]-1-cyclohexanone (12.1 %), dehydro aromadendrane (11.6 %), tetracosane (9.0 %), pentacosane (7.9 %), epoxy alloaromadendrene (5.9 %) and cyclohexadecanolide (5.8 %). The antimicrobial activity of the isolated essential oil of the plant was also investigated and it showed moderate antimicrobial and antifungal activities against Escherichia coli, Yersinia pseudotuberculosis, Pseudomonas aeruginosa, Enterococcus faecalis, Staphylococcus aureus, Bacillus cereus, Mycobacterium smegmatis and Candida albicans.